On the spectrum of rail vibration generated by a passing train - Cleante, V. G. [UNESP]; Brennan, M. J. [UNESP]; Gatti, G.; Thompson, D. J. (Elsevier, 2017)
Recent work in rail vibration has investigated methods for estimating track support stiffness from trackside vibration. This vibration, induced by the passage of a train, is mainly due to the load applied by the wheels, and is known as quasi-static excitation. It is characterized by dominant peaks in the vibration spectrum that are an integer multiple of the ratio between the speed and length of a train carriage. In this paper the behaviour of the vertical rail deflection is investigated to determine the physical reasons why the vibration at certain frequencies is greater than at others. A simple model is used to determine the contribution of the train geometry and the track parameters to the shape of the rail deflection spectrum. The model is also validated with data from various trains and at various sites. It is found that the track properties influence the range of frequencies at which there is significant vibrational energy, but the specific frequencies where there is large vibration are mainly a function of the train geometry.
Keywords: support stiffness; trackside vibration; trainload frequency